Реорганізація фрактальної структури пор у порошках детонаційних наноалмазів за високого тиску - Bulavin, L.A.; Tomchuk, O.V.; Nagornyi, A.V.; Soloviov, D.V. (Publishing house "Academperiodika", 2021)
Diamond nanoparticles have significant prospects for technological applications, so their manufacture and subsequent disaggregation are a challenging task. In this paper, the porous structure of aggregates in detonation nanodiamond powders has been analyzed using small-angle neutron scattering. The influence of high pressure allowed the contributions to the small-angle scattering from micro- and nano-sized pores to be separated. The type of fractal clusters formed by nanopores was determined. The possibility of a partial mechanical disaggregation of nanodiamond particles at a pressure of 1.5 GPa is confirmed.